Efektivitas Model Pembelajaran Problem Based Learning dalam Meningkatkan Keaktifan Belajar Siswa pada Pembelajaran Sejarah Kebudayaan Islam - Purwaningrum, Septiana; Khoiroh, Lailatul; Fani'mah, ST (LPTK UIN Syekh Wasil Kediri, 2024)
The research is motivated bt the fact un teaching the History of Islamic Culture, teachers have always liked to use conventional methods (lectures), this has had an impact on students active participation in learning, resulting in weak student learning activity. In learning, teachers don’t use interesting learning models. So that the student learning process is less conductive. This research is Clasroom Action Research, which was carried out collaboratively between the researcher and other teachers as collaborators, which consisted of two cycles and the research subjects were 20 students in class IX A of MTs Mamba’ul Ulum. This research aims to describe the process, results and response to the application of the problem based learning model to increase student learning activity in Islamic Cultural History at MTs Mamba’ul Ulum Murukan for the 2023/2024 academic year. Data collection was carried out by observing the implementation of the problem based learning model carried out by the teacher and observing in learning. The result of this research show that the problem based learning model has a positive impact on increasing students active learning. This is proven by the average value of student learning activity in each cycle, namely in cycle I it was 62,41% and cycle II it was 82,21%. This is also influenced by the teachers skills in implementing the problem based learning model, reaching 70% in cycle I and in cycle II reaching 85%. Thus, it can be concluded that the application of the problem based learning model can increase student learning activity in the Islamic Cultural History subject at MTs Mamba’ul Ulum Murukan Mojoagung.